Context Awareness in Mobile Phone Based Applications Using Bluetooth - Munnelly, Jennifer (Trinity College Dublin. Department of Computer Science, 2005)
Mobile phones have become the communication medium of choice. They have evolved into a multifaceted device capable of data services and multimedia applications in addition to their voice capabilities. Mobile phone communicative capabilities have been broadened significantly by the inclusion of technologies. Mobile phones have the potential to be useful for more complex functionality than common voice and text usage. Applications provide capabilities that allow mobile phones to learn and use information regarding their surroundings. Such behaviour is known as ?Context Awareness?. Applications are context aware when they reason about data with knowledge of their environment. These applications may behave differently depending on the context, which tends to be dynamic in mobile scenarios. Interactions between mobile devices can be made more efficient with the use of contextual inforv mation. Applications considering context awareness on mobile phones have not been explored in great detail. However, the evolving capabilities of mobile phones are inhibited by their limitations and constraints. The compactness of the embedded technology results in restricted resources like reduced processing power and battery life. Additionally, the mobility and geographical dispersion associated with mobile phone based applications incur common distributed systems issues. Concerns such as file storage and network partitioning are exacerbated by the mobile nature of the application and may act as inhibiting factors.

The objective of this dissertation is to examine the technological communication capabilities of mobile phones, and in particular, to investigate the suitability of Bluetooth as an underlying technology for communication using mobile phones. The ad-hoc nature of the short range wireless technology Bluetooth makes it suitable for dynamic personal area networks such as those formed by mobile phones. Bluetooth transport protocols lend themselves to the development of mobile phone applications which make use of data transfer techniques. This thesis illustrates an adaptive context aware mobile application that exploits the device discovery, service management and transport protocol functionality available in the Java API for Bluetooth Wireless Technology (JABWT). It also describes a communication layer capable of conveying contextual information on top of the Bluetooth stack.
Keywords: Computer Science